PENGARUH MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING COMPOSITION DENGAN MENGGUNAKAN MEDIA GAMBAR DALAM MENINGKATKAN KETERAMPILAN MENULIS DAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Harahap, Fatma Dewani (Penerbit Widina, Widina Media Utama, 2023)
This study aims to describe improving students' writing and thinking skills using the Cooperative Integrated Reading Composition learning model using picture media for fifth grade students at SD Negeri 106162 This research is a Classroom Action Research (CAR) conducted at SD Negeri 106162. Data collection uses sheets observation and evaluation test results. Based on the results of the study showed that there was an increase in students' writing skills and critical thinking. In the pre-cycle of students' writing skills, the results were 33% in the